2019
DOI: 10.3390/diagnostics9040203
|View full text |Cite
|
Sign up to set email alerts
|

Two Potential Clinical Applications of Origami-Based Paper Devices

Abstract: Detecting small amounts of analyte in clinical practice is challenging because of deficiencies in specimen sample availability and unsuitable sampling environments that prevent reliable sampling. Paper-based analytical devices (PADs) have successfully been used to detect ultralow amounts of analyte, and origami-based PADs (O-PADs) offer advantages that may boost the overall potential of PADs in general. In this study, we investigated two potential clinical applications for O-PADs. The first O-PAD we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although the reported NC paper plate needs a small amount of sample (5 μL), their method is not an autonomous technique and an expert user should follow a multistep protocol to detect the concentration of antigen in the sample. Finally, Kuo et al [ 44 ] proposed a 3D folding ELISA device to detect different concentrations of rabbit IgG. They designed four wing-shaped zones for pre-loading reagents, and a center space was set aside as a testing zone for loading samples.…”
Section: Resultsmentioning
confidence: 99%
“…Although the reported NC paper plate needs a small amount of sample (5 μL), their method is not an autonomous technique and an expert user should follow a multistep protocol to detect the concentration of antigen in the sample. Finally, Kuo et al [ 44 ] proposed a 3D folding ELISA device to detect different concentrations of rabbit IgG. They designed four wing-shaped zones for pre-loading reagents, and a center space was set aside as a testing zone for loading samples.…”
Section: Resultsmentioning
confidence: 99%
“…This control is critical for reducing variability and potential errors [17]. Our use of autonomous sequential reagent loading ensures precise timing, significantly reducing the margin for error compared to manually intensive assays, such as those reported in studies that use manually controlled paper valves [20] and origami-based designs [30]. These features ensure that each assay component interacts correctly, thus enhancing the reliability of our results.…”
Section: Superior Accuracy Through Advanced Fluid Dynamicsmentioning
confidence: 98%
“…An LOD of 255 pM was achieved with a 250 µL sample using a desktop scanner, with an assay time of 55 min [20]. Another study reported an LOD of 201 pM with an 8 µL sample, detected by a low-cost desktop scanner in 46 min [30]. Yet, another study achieved an LOD of 5.5 ng/mL (36.6 pM) using a 130 µL sample with a semi-autonomous device, and signal detection via a low-cost desktop scanner in about 1 h [23].…”
Section: Enhanced Sensitivity and Rapid Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few papers have reported the development of e-PADs for veterinary drug determination, all of which target antibiotic detection in milk samples [ 83 , 103 ]. Majority of reported e-PADs deployed optical detection methods such as colorimetry [ 104 , 105 , 106 , 107 ] and fluorescence [ 108 , 109 , 110 , 111 ].…”
Section: Applications For Food Safetymentioning
confidence: 99%